KAJIAN YURIDIS EVOLUSI PRINSIP GOOD CORPORATE GOVERNANCE MENJADI GOOD BANKING GOVERNANCE - Reka Dewantara (Fakultas Hukum Universitas Mulawarman, 2009)
A reality that Indonesia recognize as one of the state which have applying the ugly good corporate governance principal either in privat and public sector, especially on banking sector. Pricewaterhouse Cooper study show that Indonesia under sequence with China and India with value 1,96 to principal applying good corporate governance. To corrected, various effort even also do to start with reform legislation, reform of bureaucracy, socialization of applying Good Corporate Governance till founding various institution utilize to support applying Good Corporate Governance, good policyy from Bank of Indonesia and Institution-institution which of initiative by stakeholders and share holders.